1958
DOI: 10.1042/bj0690012
|View full text |Cite
|
Sign up to set email alerts
|

The charged groups at the interface of some blood cells

Abstract: J. J. CONNELL I958 3. Actomyosin is extractable from very fresh codling muscle at ionic strengths as low as 0 1 and pH 7 5, but quickly becomes insoluble. It is not extractable from fish under the same conditions after rigor mortis. 4. Monodisperse myosin is present in extracts of codling muscle made at an ionic strength of 0-3 or higher, pH 6-5 and 7-5. 5. Codling myosin is extremely labile and rapidly aggregates either on standing in the cold or during precipitation. The assistance of Mr P. F. Howgate in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
0
2

Year Published

1960
1960
1995
1995

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(52 citation statements)
references
References 28 publications
5
45
0
2
Order By: Relevance
“…If radial calcium "bridges" are involved in the adhesion of ascites cells to peritoneal cells, it is difficult to understand why they are not involved in promoting mutual adhesions between the tumor cells. In assessing the role of calcium-binding in tumor cells, it must not be forgotten that the data of Bangham et al (11,12) also indicate that in isolated liver cells this binding is as poor as it is in Ehrlich ascites tumor cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If radial calcium "bridges" are involved in the adhesion of ascites cells to peritoneal cells, it is difficult to understand why they are not involved in promoting mutual adhesions between the tumor cells. In assessing the role of calcium-binding in tumor cells, it must not be forgotten that the data of Bangham et al (11,12) also indicate that in isolated liver cells this binding is as poor as it is in Ehrlich ascites tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…As the dissociation constants of univalent ions from anionic sites is expected to be different from that of divalent ions, it seems unlikely that anionic groups exposed by removal of calcium would be completely concealed electrically by newly bound univalent ions from the medium. Additional data revealing the poor bipding capacity of superficial anionic groups at the cell periphery come from the work of Bangham and Pethlca (11,12) who showed that very high concentrations of calcium ions are required to produce charge reversal in murine Ehrlich ascites tumor ceils. In other words, calcium is not bound at the cell surface in the sense that a surface is a two-dimensional planar structure, but is bound within the three-dimensional peripheral zone of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…This is presumably due to the removal of the adsorbed HF at alkaline pH (cf. Bangham, Pethica & Seaman, 1958). The HF activity in the eluate can be 245 recovered by re-adsorption on to fresh glass beads after neutralizing the solution with dilute HCl (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The surface of rabbit blood platelet in the physiological state was elucidated to have a negative charge and negativity was the same grade as seen in human blood (9-13) and sheep (15). Less mobility of platelet in plasma than in 0.02 M Tris saline (pH 7.5) could be attributed to the great viscosity in the plasma and interaction of the platelet surface with the plasma protein.…”
Section: Discussionmentioning
confidence: 80%
“…In fact, the surface properties of red blood cells (1)(2)(3)(4), white blood cells (5) and bacteria (6)(7)(8) have been studied by this method. The blood platelets of humans (9)(10)(11)(12)(13), horses (14) and sheep (15) have been also studied using cell electrophoresis, while those of rabbits have been neglected. Rabbit blood platelets have been used as a model system to study the storage and release of amines, especially of 5-hydroxytryptamine (5HT), since they contain relatively high amounts of 5HT com pared with other animal species.…”
mentioning
confidence: 99%